2004
DOI: 10.1074/jbc.m408959200
|View full text |Cite
|
Sign up to set email alerts
|

A TRPC1/TRPC3-mediated Increase in Store-operated Calcium Entry Is Required for Differentiation of H19-7 Hippocampal Neuronal Cells

Abstract: Store-operated calcium entry (SOCE) and TRPC protein expression were investigated in the rat-derived hippocampal H19-7 cell line. Thapsigargin-stimulated Ba 2؉ entry and the expression of TRPC1, TRPC3, TRPC4, TRPC5, TRPC6, and TRPC7 mRNA and protein were observed in proliferating H19-7 cells. When cells were placed under differentiating conditions, a change in TRPC homolog expression profile occurred. The expression of TRPC1 and TRPC3 mRNA and protein dramatically increased, while the expression of TRPC4 and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(143 citation statements)
references
References 35 publications
6
135
1
1
Order By: Relevance
“…Recently, a study reported that a ryanodine-sensitive receptor (RyR) agonist, caffeine, stimulates Ca 2ϩ response that increases throughout neuronal differentiation in embryonic P19 carcinoma stem cells (CSCs) and adult murine MSCs (43). Intracellular Ca 2ϩ concentration has been demonstrated to be controlled by multiple mechanisms, including well characterized Ca 2ϩ influx through voltage-gated channels, ligand-gated channels (44,45), and non-voltage-gated channels (14), as well as Ca 2ϩ releasing from the endoplasmic reticulum (ER) via intracellular RyR and IP 3 R (15). Here, we uncovered for the first time that the intracellular Ca 2ϩ contents could be regulated by a PcG protein, EZH2, through modulating the gene expression of PIP5K1C in addition to above mentioned calcium channels (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study reported that a ryanodine-sensitive receptor (RyR) agonist, caffeine, stimulates Ca 2ϩ response that increases throughout neuronal differentiation in embryonic P19 carcinoma stem cells (CSCs) and adult murine MSCs (43). Intracellular Ca 2ϩ concentration has been demonstrated to be controlled by multiple mechanisms, including well characterized Ca 2ϩ influx through voltage-gated channels, ligand-gated channels (44,45), and non-voltage-gated channels (14), as well as Ca 2ϩ releasing from the endoplasmic reticulum (ER) via intracellular RyR and IP 3 R (15). Here, we uncovered for the first time that the intracellular Ca 2ϩ contents could be regulated by a PcG protein, EZH2, through modulating the gene expression of PIP5K1C in addition to above mentioned calcium channels (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether intracellular Ca 2ϩ signaling is required for neuronal differentiation from hMSCs remains unclear. The expression of transient receptor potential (TRP) proteins, TRPC1 and TRPC3, is elevated to activate store-operated calcium entry (SOCE) after differentiation of H19 -7 hippocampal neuronal cells (14). It is also known that inositol 1,4,5-trisphosphate (IP 3 ) stimulates a ligand-gated channel, IP 3 receptor (IP 3 R), to release Ca 2ϩ from intracellular stores in neurons (15).…”
Section: Human Mesenchymal Stem Cells (Hmscs)mentioning
confidence: 99%
“…During the experiment, the perfusion was stopped, and 1 ml of 2, 10, or 20 g/ml ALO or 2 or 10 M ionomycin was added to 1 ml of HBSS within the perfusion chamber. Intracellular fura2 fluorescence was measured every 10 s for up to 30 min, using the epifluorescent imaging system previously described (34). Determination of free intracellular Ca 2ϩ in the samples was calculated by correlating the ratio of fura2 fluorescence at 340 and 380 nm to the 340/380 ratios obtained from a Ca 2ϩ standard curve.…”
Section: Methodsmentioning
confidence: 99%
“…Highly discrepant results obtained in heterologous expression studies and the inability to reproducibly reconstitute native capacitative Ca 2+ entry channels by overexpression of a TRPC species led to the hypothesis that TRPC proteins are pore-forming subunits, which may require association with unidentified endogenous proteins to form a SOCE (or CCE) channel (Sinkins et al 1998;McKay et al 2000). This concept was later on continuously supported by studies using antisense and siRNA knock-down strategies or expression of dominant negative TRP species to suppress or modify endogenous SOCE (Groschner et al 1998;Liu et al 2000;Philipp et al 2000;Wu et al 2000;Baldi et al 2003;Liu et al 2003;Wu et al 2004) and appears reasonable and sufficient to explain the phenomenon that expression of a TRPC species generates divergently regulated Ca 2+ entry pathways in different cell systems or even in one host cell type at different levels of expression . The concept implies that a given TRPC species is able to associate with other channel and auxiliary subunits to form distinct signaling complexes with a composition dependent on the availability of the complex partners.…”
Section: Introductionmentioning
confidence: 99%